Green synthesis and characterization of 3-carboxycoumarin and ethylcoumarin-3-carboxylate via Knoevenagel condensation - Syed Salman, Shafqat; Amirazam, Khan; Misbahulain, Khan; Shanti Faridah, Salleh; Mohd Syahmi, Jamaludin; Pang, Suh Cem (Chemical Publishing Co, 2017)
Environmentally benign, simple, efficient and clean syntheses of 3-carboxycoumarins and ethyl coumarin-3-carboxylate have been synthesized via Knoevenagel condensation using green catalysts such as aqueous extract of Acacia concinna pods and amino acids. These syntheses were carried out in solvents as well as solvent-less media. The yields obtained (between 86 % to 96 %) for the reactions were equal or better than those previously reported. The products were isolated, purified and characterized through melting points, TLC, IR, GC Mass and 1H NMR spectroscopy. The characterized molecules showed structural and compositional conformity with the predicted reactions. The green route used for these reactions has shown to be efficient in reducing the time of reaction and in avoiding the toxic nature of the catalysts employed in classical reaction